2016
DOI: 10.4103/1305-7456.178294
|View full text |Cite
|
Sign up to set email alerts
|

Halitosis: Current concepts on etiology, diagnosis and management

Abstract: Halitosis or oral malodor is an offensive odor originating from the oral cavity, leading to anxiety and psychosocial embarrassment. A patient with halitosis is most likely to contact primary care practitioner for the diagnosis and management. With proper diagnosis, identification of the etiology and timely referrals certain steps are taken to create a successful individualized therapeutic approach for each patient seeking assistance. It is significant to highlight the necessity of an interdisciplinary method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
109
1
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 53 publications
(84 reference statements)
0
109
1
20
Order By: Relevance
“…Dry mouth has been found to be associated with oral malodour, which can be explained by the reduced salivary flow favouring anaerobic bacterial putrefaction of food debris that remains in the oral cavity after eating . Dry mouth also results in an increased Gram‐negative bacterial load, which increases VSC production, the main contributor to halitosis . This is especially evident in the morning as salivary flow has decreased during the sleeping period; as demonstrated in 70% of participants in a study in Baghdad, Iraq…”
Section: Risk Factors For Halitosismentioning
confidence: 99%
See 4 more Smart Citations
“…Dry mouth has been found to be associated with oral malodour, which can be explained by the reduced salivary flow favouring anaerobic bacterial putrefaction of food debris that remains in the oral cavity after eating . Dry mouth also results in an increased Gram‐negative bacterial load, which increases VSC production, the main contributor to halitosis . This is especially evident in the morning as salivary flow has decreased during the sleeping period; as demonstrated in 70% of participants in a study in Baghdad, Iraq…”
Section: Risk Factors For Halitosismentioning
confidence: 99%
“…The VSCs also aid bacterial invasion of the connective tissue by their toxic effects on epithelial cells, while methyl mercaptan hinders epithelial cell growth and proliferation . This is accentuated by decreasing oxygen tension arising from an increase in periodontal pocket depth, with a concomitant decrease in pH, which is necessary for the putrefaction of amino acids that create VSCs . It has also been suggested that saliva from patients that suffer from periodontal disease might produce increased amounts of VSCs …”
Section: Sources Of Halitosismentioning
confidence: 99%
See 3 more Smart Citations